Endothelial Notch signaling controls insulin transport in muscle. Issue 4 (18th March 2020) - Hasan, Sana S; Jabs, Markus; Taylor, Jacqueline; Wiedmann, Lena; Leibing, Thomas; Nordström, Viola; Federico, Giuseppina; Roma, Leticia P; Carlein, Christopher; Wolff, Gretchen; Ekim‐Üstünel, Bilgen; Brune, Maik; et al.
Abstract: The role of the endothelium is not just limited to acting as an inert barrier for facilitating blood transport. Endothelial cells (ECs), through expression of a repertoire of angiocrine molecules, regulate metabolic demands in an organ‐specific manner. Insulin flux across the endothelium to muscle cells is a rate‐limiting process influencing insulin‐mediated lowering of blood glucose. Here, we demonstrate that Notch signaling in ECs regulates insulin transport to muscle. Notch signaling activity was higher in ECs isolated from obese mice compared to non‐obese. Sustained Notch signaling in ECs lowered insulin sensitivity and increased blood glucose levels. On the contrary, EC‐specific inhibition of Notch signaling increased insulin sensitivity and improved glucose tolerance and glucose uptake in muscle in a high‐fat diet‐induced insulin resistance model. This was associated with increased transcription of Cav1, Cav2, and Cavin1, higher number of caveolae in ECs, and insulin uptake rates, as well as increased microvessel density. These data imply that Notch signaling in the endothelium actively controls insulin sensitivity and glucose homeostasis and may therefore represent a therapeutic target for diabetes. Synopsis: Insulin flux from blood plasma to muscle cells across the endothelium is a critical step in insulin‐mediated lowering of blood glucose levels. This study highlights the role of Notch signaling in regulating systemic glucose homeostasis. Notch signaling activity was higher in endothelial cells (ECs) isolated from obese mice compared to non‐obese mice. Sustained Notch signaling in ECs lowered insulin sensitivity and increased blood glucose levels in mice. EC‐specific inhibition of canonical Notch signaling increased insulin sensitivity and improved glucose tolerance in a high‐fat diet‐induced insulin resistance model. Glucose tolerance improvement was associated with increased transcription of genes involved in caveolae formation (Cav1 and Cavin1), higher number of caveolae in ECs and insulin uptake rates. Abstract : Insulin flux from blood plasma to muscle cells across the endothelium is a critical step in insulin‐mediated lowering of blood glucose levels. This study highlights the role of Notch signaling in regulating systemic glucose homeostasis.